Effects of Electrochemical Activated Water During Germination on Moisture and Diastase Activities of Germinated Wheat and Paddy - Nguyen, Van Hung; Tran, Hong Anh; Vu, Thi Tho (Old Journal, 2018)
Electrochemical Activated (EA) Water has been studied and applied in many fields such as medicine, agriculture and food. Using anolyte solution pH 2.5-4.0 for disinfection allows to reduce the microorganism contamination. Catolyte solution pH 8.5-10.5 was used for soaking grains and replenishing moisture during germination. Grains were soaked at temperatures of 20, 25, 30°C to reach a moisture content of 40–43%. Study germination at 15, 20, 25°C for 4 to 6 days. Determining suitable regimen for harvesting wheat malt and paddy malt using electrochemical activated water solution, is to soak grains at 25°C and grains germination at 20°C and paddy grains soak and germination at 25°C. The results of the study showed that the activity was highest. Paddy was washed in anolyte solution, soaked in catolyte solution at 25°C, then germinated at 25°C/130 h in catolyte solution.